The Masqueraders, or Fatal Curiosity, and The Surprize, or Constancy Rewarded - Haywood, Eliza Fowler, 1693?-1756 (Book collections on Project MUSE., 2015)
"Eliza Haywood (1693-1756), the most important female English novelist of the 1720s who is famous for writing scandalous fiction about London society. Her short novels, The Masqueraders and The Surprize are valuable sources for the study of 18th century gender and identity, the social history of masquerade, the dangers of courtship and seduction, and conceptions of elite and popular cultures. Well suited to the teaching of these two texts, this volume contains annotated scholarly editions of both novels, and extensive introduction, and useful appendices that discuss the masquerade's role in 18th century debates on gender, morality, and identity."--